Human Capital and the Supply of Religion - Engelberg, Joseph; Fisman, Raymond; Hartzell, Jay C.; Parsons, Christopher A. (The Review of Economics and Statistics, 2016)
We study the role of labor inputs in religious attendance using data on Oklahoma Methodist congregations from 1961 to 2003. Pastors play a significant role in church growth: replacing a 25th percentile pastor with a 75th percentile one increases annual attendance growth by 3%. A pastor’s performance in his or her first church (largely the result of random assignment) predicts future performance, suggesting a causal effect of pastors on growth. The deployment of pastors by the church indicates efficient use of labor: low-performing pastors are more likely to be rotated or exit the sample, and high-performing pastors are moved to larger congregations.